Efficient and provably-secure certificateless sequential aggregate signature scheme - Zhu WANG; Siqi YANG; Fenghua LI; Kui GENG; Tingting PENG; Mengyao SHI (Tongxin xuebao)
Aiming at the problem that current schemes mostly let the latter signer to verify the multiple signatures of the previous signer, and the message is signed and then passed to the next signer, leading to the efficiency problem of long overall signature time.A sequential aggregate signature scheme based on bilinear pairs was proposed.The aggregate signatures of documents were generated by multiple users in a certain order, and only the final signature was needed to be verified to confirm the correct order of signatures and the legitimacy of multiple user signatures.The complexity of verifying the multi-user sequential signature was effectively reduced and the offline verification of the authenticity of signature was realized when the user was offline or in a delay-tolerant network with limited node caching capacity and network resources.It is shown that the proposed scheme is existential unforgeability against chosen-message attacks under adversary adaptive selection messages in the random oracle model.